2022
DOI: 10.1161/str.53.suppl_1.74
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 74: Area Deprivation Index, Stroke Outcomes, And Structural Changes To Improve Access To Thrombectomy

Abstract: Introduction: In New York City (NYC), expanding the reach of thrombectomy-capable stroke centers (TSC) is key to combating socioeconomic disparities in stroke care. The Area Deprivation Index (ADI), a validated, neighborhood-level composite measure (scored 1-100) that includes income, education, employment, and housing quality, has informed healthcare delivery but has not been used to identify disadvantaged neighborhoods with poor access to stroke care. We sought to evaluate the impact of establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For instance, in one study, higher ADI was associated with longer times from ambulance arrival to groin puncture for thrombectomy. 27 Another study in South Korea also found that neither low area-level socioeconomic status nor urbanization was associated with prehospital delay; however, low socioeconomic status in urban areas was related to delay. 28 The latter study, unlike ours, did not account for distance to treating hospital and generalizability to the US sociodemographic landscape may be limited.…”
Section: Some Of the Factors Associated With Delays In Ed Presentationmentioning
confidence: 96%
“…For instance, in one study, higher ADI was associated with longer times from ambulance arrival to groin puncture for thrombectomy. 27 Another study in South Korea also found that neither low area-level socioeconomic status nor urbanization was associated with prehospital delay; however, low socioeconomic status in urban areas was related to delay. 28 The latter study, unlike ours, did not account for distance to treating hospital and generalizability to the US sociodemographic landscape may be limited.…”
Section: Some Of the Factors Associated With Delays In Ed Presentationmentioning
confidence: 96%